Strategi Bhabinkamtibmas dalam Upaya Optimalisasi Penerapan Program Door To Door System (Studi Kasus Polsek Menganti) - Ramadhan N (Airlangga Development Journal, 2018)
The situation of security and public order is highly expected by the entire community to be realized, thus giving rise to a sense of peace and peace for every community and  can  increase motivation and  enthusiasm for work. Implementation  of the Community Policing  Program in  the midst of the community was carried out by the Police in Gresik. The purpose of this study was to analyze the Bhabinkamtibmas strategy in an effort to optimize the application of door to door system programs. The research method used is a qualitative approach, which uses data collection techniques in the form of interviews, observation and documentation. The results of the study indicate that the community Policing strategy in an effort to optimize the implementation of the door-to-door system program is by rolling out personnel  from one  village  to  another;  do  various door  to  door  system activities; attach police aid stickers to the homes of community leaders; empowerment of local wisdom, as well as the vigorous socialization of police of community partners to eliminate the image of the military police.